2015
DOI: 10.1007/s11356-015-5497-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle pollution and associated increasing potential risks on environment and human health: a case study of China

Abstract: The aims of this study are (1) to discuss the mechanism of nanoparticle lifecycle and estimate the impacts of its associated pollution on environment and human health; and (2) to provide recommendation to policy makers on how to leverage nanopollution and human health along with the rapid development of economics in China. Manufactured nanoparticles (MNPs) could either directly or indirectly impair human health and the environment. Exposures to MNP include many ways, such as via inhalation, ingestion, direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Inorganic nanoparticles, e.g. nano-silver particles [2], have been verified to be highly effective to MDR bacteria, nevertheless this type of antimicrobial agents have potential threats to human health and environment [4]. Many new antibiotics and antimicrobial peptides have been developed for dealing with continuously-emerging MDR bacteria, but the developing rate of novel antimicrobial agents cannot catch up with the enhancement of antibiotic resistance of MDR bacteria through bacterial surface modification, protease secretion and expression of efflux pumps [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanoparticles, e.g. nano-silver particles [2], have been verified to be highly effective to MDR bacteria, nevertheless this type of antimicrobial agents have potential threats to human health and environment [4]. Many new antibiotics and antimicrobial peptides have been developed for dealing with continuously-emerging MDR bacteria, but the developing rate of novel antimicrobial agents cannot catch up with the enhancement of antibiotic resistance of MDR bacteria through bacterial surface modification, protease secretion and expression of efflux pumps [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The existing chemical nanoparticles, e.g., carbon nanotubes, are also able to produce toxic effects (PourGashtasbi, 2015). It is argued that natural nanoparticles are not considerable as a new phenomenon because they come from daily human activities like mining, cooking, and combustion of materials (Gao et al, 2015). Nanoparticle studies have shown that they have some special properties, i.e., (1) ultrasmall-sized particles have extreme mobility and higher propagation in living organisms if not controlled, (2) they can create more toxic effects per unit compared to larger particles of the same chemicals, (3) they can be absorbed more quickly by cells, and (4) they move more quickly, contaminating the environment through air, soil, and water, leading to damage of plants and animals (Baalousha and Lead, 2013).…”
Section: Challenge To Usage and Management Of Nanoparticlesmentioning
confidence: 99%
“…With the wide use of nanomaterials, large numbers of engineered nanoparticles (ENPs) are discharged into the water and soil system [1,2]. TiO 2 -NPs, ZnO-NPs and CuO-NPs are common metal oxide nanoparticles (MNPs) used in plant growth, cosmetics, surface coating and sunscreens, etc., and the biotoxicity and the environmental risk of these metal oxide nanoparticles has caused extensive concern in recent years [3,4]. For example, CuO nanoparticles caused a significant decrease in rice seed germination percentage [5], and 1000 mg L-1 ZnO-NPs could reduce the root length of corn and cucumber [6].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 -NPs significantly reduced the toxic effects of tetracycline on rice in terms of its fresh biomass and levels of antioxidant enzymes [15]. Most of the studies about the effect of nanoparticles on heavy metals behaviour were conducted in hydroponic conditions, and only a few were conducted in soil conditions [4,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%